An introduction to the viable systems approach and its contribution to marketing - Sergio Barile; Jaqueline Pels; Francesco Polese; Marialuisa Saviano (jbm - Journal of Business Market Management, 2012)
Organizations are increasingly challenged by dynamism and turbulence that determine conditions of complexity in decision making. The aim of this paper is to highlight the need for a general frame of reference for management and marketing and to justify why adopting a systems approach is adequate at both theoretical and practical level. Specifically, the purpose of this paper is to explain why a systems approach is needed to understand business and market dynamics, and why the VSA may represent a good integrator of management and marketing theories and practices. The paper begins with a brief review of systems theories that have been proposed in the general context of management and marketing. It proceeds by illustrating the fundamental principles and concepts of the VSA and its contribution to marketing. The paper closes by discussing future research avenues and suggesting implications for researchers and practitioners.
urn:nbn:de:0114-jbm-v5i2.140
Keywords: 650; systems thinking; viable systems approach; marketing; Systemtheorie; Komplexe Systeme; Marketing; Wissenschaftliche Methode